THE SYSTEM OF SPIRITUAL EDUCATION OF TAREKAT SAMMANIYAH AT LEARNING ASSEMBLY OF IHYA ULUMUDDIN MEDAN - Arifin Arifin; Hasan Asari; Amroeni Drajat (State Islamic University of North Sumatra Indonesia, 2017)
This study aimed to discover 1) the goal of spiritual education of Tarekat Sammaniyah at Learning Assembly of Ihya Ulumuddin Medan, 2) the contents of spiritual education of Tarekat Sammaniyah at Learning Assembly of Ihya Ulumuddin Medan, 3) The Method of spiritual education of Taretkat Sammaniyah at Learning Assembly of Ihya Ulumuddin Medan, 4) The teachers/ Fasilitators of spiritual education of Tarekat Sammaniyah at Learning Assembly of Ihya Ulumuddin Medan, 5) The Students of spiritual education of Tarekat Sammaniyah at Learning Assembly of Ihya Ulumuddin Medan, 6) Facilities and infrastuctures of Tarekat Sammaniyah at Learning Assembly of Ihya Ulumuddin Medan. This study used the qualitative research approach. The data was taken through intervew, observation and also takng documentation. The informan of this study was the principle concurently teacher (Called by Mursyid), Assistant of teacher (called by Khalifah), Students (Called by Salik) of Tarekat Sammaniyah at Learning Assembly of Ihya Ulumuddin Medan. The data analysis was done by data reduction, presentation of the data and data verification. The results of this study were; 1) The aim of spiritual education was to know Allah, to remember, and also to look Allah by purification of the soul (Tazkiyatun Nafsi) and draw closer to the God (Allah) by cleansing the heart (Taqorrub Ilallah), 2) The contents of spiritual education were about Islam, faith, goodness, Syari’at, Hakikat, Ma’rifat and also Zikir (Remember of the God), 3) The method were bai’at, lecturing, remembering (rabithah, kafi’at, tawajjuh, khalwat /suluk), 4) The Mursyid was one who led and taught and also developed the Tarekat , he has an unbroken lineage up to Prophet, Jibril and Allah SWT. The level were; Syekh/Buya/Father, Vice Mursyid (Khalifah), Firstly, the Old Khalifah, Secondly, The young Khalifah. The qualities that must be possessed by the Mursyid / vice Mursyid were namely: pious, wise, be patient and merciful nature, able to keep secrets, trust, discipline, guarding the lust of the worldly desire, sincere heart, should not be disappointed seeing the students who have not succeeded yet, Maintaining self-esteem, prestige, may provide certain clues in certain circumstances, 5) The Students were people who have been sworn, and before being sworn, they should bathe taubat, pray taubat, and also pray hajat to study knowledge to Mursyid. The level of students/ Salik were mubtadi, mutawashithah, muntahi, 6) The facilities and infrastructures were Mosque, The Guest room for whom it may stay overnight, sound system, Suluk place, ablution place, tasbih, curtain for seclusion (khalwat).